2016
DOI: 10.1038/ng.3518
|View full text |Cite
|
Sign up to set email alerts
|

OsSPL13 controls grain size in cultivated rice

Abstract: Although genetic diversity has a cardinal role in domestication, abundant natural allelic variations across the rice genome that cause agronomically important differences between diverse varieties have not been fully explored. Here we implement an approach integrating genome-wide association testing with functional analysis on grain size in a diverse rice population. We report that a major quantitative trait locus, GLW7, encoding the plant-specific transcription factor OsSPL13, positively regulates cell size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
446
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 622 publications
(483 citation statements)
references
References 50 publications
10
446
1
Order By: Relevance
“…This finding is consistent with previous reports that attributed natural variation in tomato fruit size and rice grain size to expression variation in Sl-KLUH and OsSPL13, respectively (Chakrabarti et al, 2013;Si et al, 2016). Genetic complementation tests with four transgene constructs representing four haplotypes (II, III, IV, and OX) showed that the TS66 loss-of-function haplotype cannot be complemented by Sl-ALMT9 alleles from haplotype construct II, which indicates that construct II haplotypes also represent loss-of-function alleles.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with previous reports that attributed natural variation in tomato fruit size and rice grain size to expression variation in Sl-KLUH and OsSPL13, respectively (Chakrabarti et al, 2013;Si et al, 2016). Genetic complementation tests with four transgene constructs representing four haplotypes (II, III, IV, and OX) showed that the TS66 loss-of-function haplotype cannot be complemented by Sl-ALMT9 alleles from haplotype construct II, which indicates that construct II haplotypes also represent loss-of-function alleles.…”
Section: Discussionsupporting
confidence: 83%
“…Two of the three genes involved in microtubule-based process, and another one associated with glycolytic pathway and expressed in response to abiotic stress. Recently, many novel genes have been cloned as a result of GWAS (Duan et al 2017, Si et al 2016Yano et al 2016). However, in our study, because the genotype was from the 5K SNPs array, the SNPs density was insufficient to cover every gene.…”
Section: Identification Of Candidate Gene Controlling Cold Tolerancementioning
confidence: 92%
“…In addition, GWAS may not be able to detect the phenotypic effects of rare alleles (present at very low frequencies in the populations studied) and GWAS detection power may decrease in the case of loci involving multiple allelic variants (Morris and Kaplan 2002), which may explain why GWAS have only unraveled a small portion of phenotypic variance (Zuk et al 2014). Despite these constraints, GWAS have been successfully used to dissect complex traits in many crop species including maize (Buckler et al 2009), sorghum (Morris et al 2013) and rice (Huang et al 2010; Zhao et al 2011; Huang et al 2012; Courtois et al 2013; Huang et al 2015; Si et al 2016; Yano et al 2016). Incorporation of GWAS information in genomic selection models has also proved able to improve the accuracy of predictions and should consequently be used in rice breeding programs (Spindel et al 2015; Spindel et al 2016).…”
Section: Introductionmentioning
confidence: 99%